Peran Pengalaman Usaha dalam Memoderasi Pengaruh Zakat Produktif dan Motivasi terhadap Perkembangan Usaha (Studi pada Mustahiq LAZ Harapan Umat Boyolali) - Hendro Guntoro; Mochlasin (Universitas Muhammadiyah Surabaya, 2023)
This research was conducted at the LAZ Harapan Umat Boyolali institution. The purpose of this study was to determine the effect of productive zakat and business motivation on mustahiq business development. As well as knowing the role of business experience in moderating the effect of productive zakat and motivation on mustahiq business development. The method used in this research is quantitative research with primary data sources obtained through distributing questionnaires. The sample technique used is purposive sampling, which is a non-random sampling method and the sample is selected in accordance with predetermined standardization. The sample taken was 45 respondents. The results of this study indicate that the variables of productive zakat and business motivation have a positive and significant influence on mustahiq business development. Then business experience is not able to moderate the influence of productive zakat and business motivation on mustahiq business development.